PENGARUH KEBIJAKAN MONETER TERHADAP PERTUMBUHAN EKONOMI GLOBAL DI INDONESIA - Rifin, Rifin; Fiton, Fiton; Nurfika, Nurfika; Putra, Faturachman Al; Asriani, Asriani (LP2M Universitas Bina Bangsa, 2025)
This study aims to understand and analyze the influence of monetary policy on global economic growth. Through a review of literature and interpretation of findings from various studies, this research evaluates the development of research on this topic from 2020 to 2023. The study also identifies core journals that contain research results on this topic and conducts a bibliometric analysis of the development of research on this topic using VOSviewer. The results show an increase in the number of research publications from 2020 to 2023, with the highest number of publications occurring in 2023. The bibliometric analysis also indicates that several topics in forensic audit research have not been extensively studied, which could be potential areas for future research. In conclusion, this study provides new insights into the influence of monetary policy on global economic growth and highlights the importance of the systematic literature review method and bibliometric analysis in this research